Reassessing Al-Suyūṭī’s Claim of Tawqīfiyyah in Surah Naming: A Critical Analysis of Al-Itqān fī ʿUlūm al-Qurʾān - Eva Nugraha; Sahroni; Kholik Ramdan Mahesa (Refleksi: Jurnal Kajian Agama dan Filsafat, 2025)
This study critically examines al-Suyūṭī’s claim that all surah names in the Qur’an are tawqīfī, a theme that has received limited scholarly attention. Using a descriptive-analytical method, this article classifies al-Suyūṭī’s arguments in Al-Itqān fī ʿUlūm al-Qurʾān and evaluates them based on the presence or absence of reliable prophetic or companion-based reports. The primary source for this research is Al-Itqān, supported by secondary literature from contemporary studies on Qur’anic sciences. The findings show that al-Suyūṭī’s arguments can be divided into two major categories: surah names supported by authentic hadith, and those derived from scholarly usage without strong textual basis. This study argues that al-Suyūṭī’s assertion of tawqīfiyyah is not fully supported by his own evidence, indicating inconsistencies in his methodological approach. The research contributes to Qur’anic studies by offering a more nuanced understanding of the historical development of surah naming and highlighting the interplay between revelation-based and ijtihād-based nomenclature.